Neisseria gonorrhoeae resistance test against cefixime in gonorrhea patients in Surabaya - Amalia Rositawati; S. Sawitri; Afif Nurul Hidayati (PAGEPress Publications, 2019)
Gonorrhea remains as one of the most common sexually transmitted diseases in developing countries. The third generation cephalosporin such as cefixime is now one of the first-line therapies in many regions. Over the last decade, strains of Neisseria gonorrhoeae have been reported to develop high levels of resistance against several antimicrobial agent cefixime. The purpose of this study is to evaluate the susceptibility of cefixime to Neisseria gonorrhoeae. Methods: The study design was descriptive laboratory observational cross sectional from June 2017 to September 2017. Twenty isolates Neisserria gonorrhoeae taken from outpatients with positive complaints of purulent secretions, who visited 7 Community Health Centre in Surabaya and met the inclusion criterias, were tested with cefixime diffusion susceptibility test. Results: 7 of 20 isolates (35%) were resistant to cefixime and 13 of 20 isolates (65%) sensitive to cefixime. Conclusions: Neisseria gonorhoeae strain was proven to be resistant to cefixime by performing diffusion test.